2000
DOI: 10.1063/1.126442
|View full text |Cite
|
Sign up to set email alerts
|

High-quality strain-relaxed SiGe alloy grown on implanted silicon–on–insulator substrate

Abstract: We report on the growth and characterization of high-quality strain-relaxed SiGe alloys on a compliant silicon–on–insulator (SOI) substrate. The annealing temperature required for strain transfer has been reduced through boron implantation to the buried oxide, leading to a high quality SiGe alloy free from dislocations as evident from the near-band gap photoluminescence. Nearly complete strain relaxation (∼95%) for SiGe alloy of a thickness beyond the conventional critical thickness has been obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Several attempts have been made to fabricate SGOI substrates. Huang et al utilized an ultrathin SOI as a ''compliant substrate'' to partially relax an initially strained SiGe film [2,3]. An et al carried out low-energy separation by implantation of oxygen (SIMOX) in a strained-relaxed SiGe virtual substrate [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts have been made to fabricate SGOI substrates. Huang et al utilized an ultrathin SOI as a ''compliant substrate'' to partially relax an initially strained SiGe film [2,3]. An et al carried out low-energy separation by implantation of oxygen (SIMOX) in a strained-relaxed SiGe virtual substrate [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The underlying physical principle of a compliant substrate is to utilize the compliance of the substrate to release the misfit strain in a thin film on top of it without the generation of dislocations. There have been various ways to realize compliant substrates, including wafer bonding, 2 glass transformation through ion implantation 3 and other methods. 4,5 For various silicon-based heterostructural devices, a substrate template for subsequent epitaxy is often desired with a lattice constant between that of silicon and germanium.…”
Section: Introductionmentioning
confidence: 99%
“…Thus we annealed our samples at 800 1C which was lower than the thermal tolerance of Si 1Ày C y films [12] but we could not find the progress of strain relaxation. Huang et al [13] reported that the relaxation ratio corresponded to the values estimated from the strain partitioning theory after the annealing at 850 1C using B-doped SOI substrates which allow to reduce the annealing temperature. In order to discuss the ''freestanding'' theory in our experiment, we also need to adopt some methods to reduce the annealing temperature.…”
Section: Resultsmentioning
confidence: 91%